Kunci Kinerja Karyawan: Peran Kepribadian, Budaya Organisasi dan Keadilan Organisasi - Sekar Asmara Jayaning Diah; Veimina Surya; Chandra Megah; Roro Kusnabilla Erfa; Dian Gema Rizkia; Rokiah Kusumapradja; Wahyuni Dian Purwati; Rian Adi Pamungkas (Jurnal Manajemen dan Organisasi, 2022)
This study is based on the occurrence of 63 cases of undesirable events in RSIA X which illustrates a poor work result in health organizations such as hospitals. The purpose of this study is to empirically reveal the influence of personality, organizational culture and organizational justice on employee performance. The method used is a cross sectional study and uses a unit of analysis of 180 employees as respondents. The results of the analysis conclude that simultaneously and partially personality, organizational culture and organizational justice have a positive and significant effect on performance, and these three variables contribute as much as 66,9 percent in improving employee performance.